Dissolution and Passivation of a Silicon-Rich Austenitic Stainless Steel during Active-Passive Cycles in Sulfuric and Nitric Acid. Issue 13 (7th November 2017) - Laurent, Barbara; Gruet, Nathalie; Gwinner, Benoit; Miserque, Frederic; Rousseau, Karine; Ogle, Kevin
Abstract : The high Si containing X1CrNiSi18-15-4 stainless steel (SS) spontaneously forms a protective oxide film that is mostly composed of mixed chromium and silicon oxides. This film ensures a good durability of the industrial facilities the alloy was designed for, containing very acidic electrolytes such as hot and concentrated nitric acid, HNO3, in presence of oxidizing species. In the present work, the chemistry of the oxide formed and the passivation kinetics of the alloy in sulfuric acid, H2 SO4, and for the first time in HNO3, were monitored by atomic emission spectroelectrochemistry (AESEC) over successive activation and passivation cycles of the material. X1CrNiSi18-15-4 SS was compared to a low Si containing SS, the X2CrNiN18-10 SS. It was found that a similar quantity and rate of passive film was formed during passivation, and dissolved during activation. Reproducible results were obtained over several active-passive cycles. The excess Cr was correlated with the dissolution rate decay during passivation. The Si/Cr ratio of the passive film was determined by X-ray photoelectron spectroscopy, energy dispersive X-ray spectroscopy (performed using transmission electron microscopy), and AESEC giving similar results within experimental error. The EDX profile suggest that the passive film consists of a Si rich outer and Cr rich inner layer.